2017
DOI: 10.4236/ce.2017.811118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Specialist Medical Training in Internal Medicine between Germany, Austria and Switzerland: An Overview

Abstract: Specialists for internal medicine are very important group of the medical profession. Although they make up the largest group of specialized physicians, there is a shortage of physicians, and in particular of internists in Germany, Austria and under some aspects in Switzerland. Germany, Austria and Switzerland show also an intensive transfer of physicians. It is therefore of interest to investigate if the tern "internist" in the three countries under consideration is based on the same or equivalent education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In Romania, a strong correlation between the number of requests for certificates of conformity and the economic crisis was evident in 2010, when the hardest effects of the crisis were felt in Romania and more than 2500 certificates were issued (Galan, Olsavszky, & Vlădescu, 2011). This leads to the findings of Braun and Gresser (2017), that stated that in 2012 the highest numbers of European doctors who migrated to Germany were those trained in Romania, with 2704 doctors. In the same year Romania had only 39,813 doctors, a very low number taking into account that in 1990 there were 55,000 physicians working there (Boboc, Boncea, & Boboc, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…In Romania, a strong correlation between the number of requests for certificates of conformity and the economic crisis was evident in 2010, when the hardest effects of the crisis were felt in Romania and more than 2500 certificates were issued (Galan, Olsavszky, & Vlădescu, 2011). This leads to the findings of Braun and Gresser (2017), that stated that in 2012 the highest numbers of European doctors who migrated to Germany were those trained in Romania, with 2704 doctors. In the same year Romania had only 39,813 doctors, a very low number taking into account that in 1990 there were 55,000 physicians working there (Boboc, Boncea, & Boboc, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…The European IM Examination Board conducted one of the few studies on this topic in 2013, showing some similarities and also highlighting great differences in the framework, content and governance of training among European countries. 7 To the best of our knowledge, there are currently no studies that comprehensively compare different IM training pathways worldwide. 6 In 2016, Braun et al carried out a comparative study of IM training periods in Germany, Austria and Switzerland, and reported a reasonable degree of uniformity among them.…”
Section: And Inmentioning
confidence: 99%
“…6 In 2016, Braun et al carried out a comparative study of IM training periods in Germany, Austria and Switzerland, and reported a reasonable degree of uniformity among them. 7 To the best of our knowledge, there are currently no studies that comprehensively compare different IM training pathways worldwide.…”
Section: And Inmentioning
confidence: 99%